2017
DOI: 10.1002/pssr.201700042
|View full text |Cite
|
Sign up to set email alerts
|

Growth mechanism of InGaN nanodots on three‐dimensional GaN structures

Abstract: In this study, we investigated the growth mechanism of indium gallium nitride (InGaN) nanodots (NDs) and an InGaN layer, which were simultaneously formed on a three‐dimensional (3D) gallium nitride (GaN) structure, having (0001) polar, (11‐22) semi‐polar, and (11‐20) nonpolar facets. We observed the difference in the morphological and compositional properties of the InGaN structures. From the high resolution transmission electron microscopy (HR‐TEM) images, it can be seen that the InGaN NDs were formed only on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It has been reported that MOVPE conditions, such as partial pressure, growth temperature, carrier gas and V/III ratio, are important parameters to determine the crystal shapes of GaN nanostructures. [6][7][8][9][10][11][12][13][14][15][16][17] Moreover, vertical-to-lateral aspect ratio of GaN nanostructure is crucial to reduce the dislocation density and markedly controlled by MOVPE conditions. According to the experiments by Lin et al 18) and Jung et al, 19) vertical growth is enhanced with increasing growth temperature under H 2 carrier gas condition, leading to high aspect ratio.…”
mentioning
confidence: 99%
“…It has been reported that MOVPE conditions, such as partial pressure, growth temperature, carrier gas and V/III ratio, are important parameters to determine the crystal shapes of GaN nanostructures. [6][7][8][9][10][11][12][13][14][15][16][17] Moreover, vertical-to-lateral aspect ratio of GaN nanostructure is crucial to reduce the dislocation density and markedly controlled by MOVPE conditions. According to the experiments by Lin et al 18) and Jung et al, 19) vertical growth is enhanced with increasing growth temperature under H 2 carrier gas condition, leading to high aspect ratio.…”
mentioning
confidence: 99%